Pendampingan Bisnis Provider Internet dalam Meningkatkan Profitabilitas Menuju Layanan Internet Profesional - Mauliana, Phitsa; Firmansyah, Ricky; Hunaifi, Nanang; Komalasari, Yunika; Sulastriningsih, R. Dewi; Dewi, Srie Wijaya Kesuma; Wiguna, Wildan (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2026)
Rapid Flash NET is a legally registered local internet service provider with 267 customers, yet it faces declining profitability, unstable cash flow, inactive customers, simple service procedures, and underdeveloped digital marketing. This community service program aimed to improve profitability, strengthen service governance, and develop digital marketing strategies toward more professional internet services. The program was conducted through needs assessment, ISP business management training, cost and profit analysis, service standard operating procedure development, network monitoring assistance, customer retention strategy, and digital marketing support. The results showed that the partner gained better understanding of cost management, service package evaluation, human resource task distribution, customer service standards, and the use of digital media for branding. The uniqueness of this program lies in its integrated approach, combining network technology, business management, finance, human resources, and marketing aspects for a legally registered mini ISP/RT-RW Net.